Developing Digital Role Play-Based Educational Learning Media through the TikTok Platform to Improve Students' Internalization of Character - Dayung Ramadhan; Bagas Mukti Nahrowi; Ali Ghufron (Research Journal on Teacher Professional Development, 2026)
This study aims to develop a digital role-play-based educational learning media through the TikTok platform to improve students' internalization of character values. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques were carried out through observation, interviews, and questionnaires with a Likert scale. The results of the study indicate that the developed media has a very high level of feasibility, with an average validation score of 4.5 from media experts and 4.6 from material experts, categorized as "very feasible." In addition, the implementation results show a significant increase in students' internalization of character values, indicated by an increase in the average score from 3.16 (before) to 4.36 (after). This increase reflects the development of students' values ​​of honesty, responsibility, cooperation, discipline, and caring. This study contributes to the field of digital character education by demonstrating that the integration of digital role-play, the TikTok platform, and the ADDIE development model provides an innovative and practical framework for fostering students’ character value internalization through interactive and contextual learning experiences.